Implementation of Cross Docking: Food Aid Distribution Program in Sigi Regency - Zulfikri, Agung (Yayasan Sinergi Kawula Muda, 2025)
Stunting remains a persistent public health challenge in disaster prone regions, particularly in Indonesia. This study investigates the implementation of cross docking logistics for the distribution of food aid to at risk households in Sigi Regency, Central Sulawesi. Employing a qualitative case study approach, data were collected through semi structured interviews with 15 logistics personnel and direct field observations. Thematic analysis was used to interpret patterns related to distribution efficiency, coordination, and infrastructure adaptation. The results demonstrate that cross docking significantly reduced distribution time from four to two days, enhanced product quality by minimizing spoilage, and improved logistical responsiveness through specialized transport and local sourcing. Inter agency collaboration and basic digital systems enabled real time data verification and ensured equitable delivery. The study highlights the practicality of cross docking in overcoming infrastructural constraints and maintaining service continuity in post disaster contexts. These findings contribute to the discourse on humanitarian logistics by illustrating the operational and public health benefits of agile distribution methods. The study suggests that cross docking, when combined with adaptive local strategies and digital integration, offers a scalable and resilient model for food aid logistics in disaster prone regions.